Asking is easy - Prashanthi, Balachander (Nanyang Technological University, 2021)
Asking is Easy is an educational campaign targeting youth aged 15-18 in response to the culture of sexual violence in Singapore. It focuses on the various aspects of consent in order to educate youth, engage them in conversation about consent, and enhance the culture of asking for consent as a preventative approach to reducing sexual violence. In an educational sphere, sexual misconduct is rampant on university campuses, with nearly half of local university graduates having experienced sexual misconduct (Teng, 2019). To make matters worse, a majority of cases go unreported. In an online sphere, digital sexual violations have become all too commonplace with telegram groups and Tumblr websites that share non-consensual images of women. For example, SG Nasi Lemak was a telegram group comprised of an estimated 44,000 members who shared thousands of inappropriate photos and videos of women without their consent (Sholihyn, 2020). This is an increasing trend, with cases of digital sexual violations having increased threefold in the last three years (Tan, 2019). These two observations inform a culture of sexual violence that needs to be addressed urgently. Framed by the Theory of Planned Behaviour, the campaign addresses four key primary research findings from surveys and interviews, namely, that 1) youth face difficulty asking for consent, 2) youth feel pressured to consent 3) youth are not sure about their ability to gauge consent, and that 4) youth learn about consent from informal learning spaces. These findings, along with secondary research regarding affirmative consent, scripts of female obligation, and coercion, informed an educational framework that was expressed via a digital campaign comprising of a website and social media.